THE SYNTAX OF TAMIANG LANGUAGE ACEH PROVINCE - Sariakin, Sariakin; Yulsafli, Yulsafli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Syntax is the study of rules for combining words into a sentence. The purpose of this research is to find out how the syntax of Tamiang language especially the sentences that are construction in the Language such as the patterns of phrases, clauses, and sentences. This research used descriptive design. The data in this research were collected through interviewing, noting and translating, recording and transcribing all utterances of Tamiang language. The number of subjects were about 24 persons. This research resulted that Tamiang language has four kinds of phrases. Meanwhile, Tamiang clauses have two forms: complete and incomplete form. The complete form has two patterns: subject-predicate and predicate -subject. Based on the parts of speech, Tamiang clauses have five forms: nominal clause, verbal clause, adjectival clause, numeral clause and prepositional clause. There are four kinds of sentences in Tamiang language: declarative sentence, imperative sentence, interrogative sentence and exclamatory sentence.Key Words: Syntax, Sentences, and Tamiang Language